PENINGKATAN KOMPETENSI IKATAN SARJANA OLAHRAGA INDONESIA MELALUI PENGKAJIAN SPORT DEVELOPMENT INDEX - Bafirman Bafirman; Hanif Badri (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
Indonesian Bachelor of Sports association organization, according to its tasks and functions, must think and work on how to improve the sports development index especially in its region and provide recommendations to policy makers to be the basis for developing future sports programs. Sport Development Index (SDI) is one of the instruments to identify the success of sports development significantly from four elements, namely; (1) Community participation in sports, (2) Facilities built for exercising (3) physical fitness, and (4) Human resources. Sports coaching in Tanah Datar District has been carried out through Sports Physical Education and Health, community sports and achievement sports. The development is carried out by involving various related elements, government, community, private sector, etc. synergistically, but with the result. still not encouraging. Seen; the relatively low number of people exercising, the limited sports facilities and infrastructure, etc. With the improvement of ISORI's organizational competence, it is expected that the Sports Flat index of Tanah Datar in the future will increase. Keywords: Sport; Development; Index; ISORI.